Autogenous biological restoration: clinical and social importance (Research, Society and Development, 2021)
The Biological Restoration technique aims to use a dental fragment as the main restorative material for the reconstruction of a fractured tooth or with an extensive carious process, which may be autogenous or homogeneous. The objective of this study is to present, through a clinical case, an autogenous biological restoration with 2-year clinical and radiographic monitoring, as an alternative method of restoring teeth with destroyed clinical crown in a 27-year-old male patient. The study was approved by the Research Ethics Committee (Number: 4.236.211). On clinical examination, it was found that tooth 16 had a temporary restoration in glass ionomer cement covering an extensive area involving the mesiopalatal cusp and the mesial crest. It was also noted that the patient had a healthy tooth 18 with no chewing function. Thus, it was proposed to make the autogenous biological restoration using tooth 18 extracted from the patient himself. Finally, after 2 years of follow-up, the restoration has good clinical applicability, showing the viability of the technique.